Understanding the Unseen Burden of Common Health Problems of School-going Children in Sub-urban Area: Insights from a Single-day Health Programme - Biswangree, Arpita; Islam, Md Fahadul; Tahsin, Rifah Sanjeedah; Raha, Rahatil Asyekin; Tabassum, Mustari Nailah; Biswangree, Bijita; Anwar, Zarrin Tasnim; Barua, Debjyoti; Mahmood, Tarannum; Imam, Md Sharif; et al. (Journal of Paediatric Surgeons of Bangladesh, 2025)
Background: Children are considered as the future leaders of a nation. But, in developing countries like Bangladesh, school-age children often face a specific burden of preventable health issues that are aggravated by poor living conditions, inadequate hygiene, and health knowledge. Objective: The study aimed to assess the common health problems among school-going children in a sub-urban area of Chattogram city, Bangladesh. Methodology This was a descriptive cross-sectional study conducted among 181 school children going to a sub-urban school in Chattogram city on April 9, 2025. A semi-structured questionnaire was used for data collection. Sociodemographic information, health practices and problems related data were recorded and analyzed. Descriptive statistics were performed using Microsoft Excel. Results: Age of the participants ranged from 5 to 16 years, with a mean age of 9.43 (±2.76). Majority of them were boys (62.43%). Deworming and immunization status were 70.17% and 33.15% respectively. Common health complaints included dental caries (46.41%), undernutrition (39.78%), dental plaque (34.81%), scabies (30.39%), and anemia (27.07%). Conclusion: Dental health problems are the commonest complaints among school-age children. The study also addressed a high burden of other preventable health conditions such as undernutrition, scabies and anemia. These findings underscore the need for regular school health screening programs and large-scale studies to improve health promotion initiatives in school level. Journal of Paediatric Surgeons of Bangladesh (2021) Vol. 12 (1 & 2):10-16